A COMPARATIVE STUDY TO ASSESS THE EFFECTIVENESS OF NORMAL SALINE DRESSING AND BETADINE SITZ BATH ON EPISIOTOMY WOUND HEALING AND EPISIOTOMY RELATED COMFORT AMONG PRIMIPARA MOTHERS IN SELECTED HOSPITAL AT ERODE DISTRICT (CAHIERS MAGELLANES-NS, 2024)
Aim: A comparative study to assess the effectiveness of normal saline dressing and betadine sitz bath on episiotomy wound healing and episiotomy related comfort among primipara mothers in selected hospital at Erode District.Methods: The investigator adopted quantitative approach with Time series design with multiple institution treatment was used for this study. This design measures the effect on the experimental group, based on their state before the beginning of the experiment (pretest) and the difference achieved at the end of the experiment (posttest). There is no control group in this design. In this method pretest was assessed after 2hours of vaginal delivery and post test was assessed on the 24hrs, 48hrs and 72 hrs of intervention. Quasi experiments are like true experiments that involve an intervention. This design lack randomization, the signature of a true experiment. The signature of a quasi experimental design is an intervention is the absence of randomization. Time series with multiple institution of treatment is useful when the researcher wants to measure the effects of a treatment over a long period of time.Results: The study reveals that level of wound healing was improved in pre test and post test group. It was found that there was significantly high improvement in wound healing after Normal saline dressing and Betadine sitz bath in the post test group. the calculated “t” value in experimental group-I was 32.450, which is greater than table value p < 0.001, and for experimental group-II the calculated “t” value was 30.476, which is greater than table value p<0.001.Conclusion: This definitely shows that Normal saline dressing is more effective than Betadine sitz bath in improving episiotomy wound healing among primi mothers.